Mpox virus-The unfolding of a public health emergency of international concern (PHEIC) - Sohail, Hamnah (Journal of the Pakistan Medical Association, 2025)
Madam, The recent declaration of the Mpox virus as a Public Health Emergency of International Concern (PHEIC) is indeed concerning.1 A PHEIC is announced when an unusual event presents a significant risk to global health through international disease transmission, necessitating a unified global response. Mpox ( Formerly Monkeypox) is a zoonotic orthopox virus that causes smallpox-like disease in humans.2 The Mpox virus has two clades: clade I (subclades: Ia and Ib) and clade II. Clade I MPXV (mortality rate: 10%), which is endemic to Central Africa, causes more severe disease than clade II MPXV.3 Currently, Clade Ib is rapidly spreading, and more than 100 laboratory-confirmed cases of Clade Ib have been reported in four non-endemic countries: Burundi, Kenya, Rwanda, and Uganda.1 This was, in part, the reason for declaring MPXV a PHIEC. Other clades are also involved in outbreaks of Mpox in several other regions.1 According to a multi-country report, clade I cases spread from human to human through intimate physical touch as well as non-sexual and sexual interaction.4 According to the same report, patients most commonly present with rash, followed by fever and genital rash. After invading the body, the virus replicates at the entry site. Then, it spreads to local lymph. Next, an initial spread of the virus in the blood leads to the seeding of other organs. Symptoms usually appear with secondary viremia.2 Recently, the first case of Mpox was detected in both Sweden and Pakistan, which underscores the need for a prompt response.5 It is likely that there are more cases of Mpox in the region. Hence, this outbreak of the Mpox virus should not be ignored. Efforts should be made to take a proactive rather than a reactive approach. International flights should be subjected to surveillance and screening for potential Mpox infection. It is important to correctly differentiate Mpox from other diseases with similar signs, symptoms and modes of transmission, like herpes and syphilis. PCR testing should be employed for diagnosis. Diagnosed cases should be closely monitored, and contact tracing should be done to prevent further cases. Since Pakistan is a low to middle income country, employing the highest level of precautionary measures is imperative. In addition, clinical collaboration with endemic countries should be strengthened. There is a significant need for sustainable efforts to manage and eradicate Mpox outbreaks.